Do elite female judokas show asymmetry in the internal and external rotators of the shoulder? A one-dimensional and principal component approach - Aedo-Muñoz, E.; Merino Muñoz, P.; Leite, L. B.; Forte, P.; Miarka, B.; Gonzalez Valenzuela, M.; Hernandez-Wimmer, C.; Arriagada-Tarifeño, D.; Brito, C. J. (Biomechanics, 2024)
Background/Aims: Asymmetry of the internal (IR) and external (ER) shoulder rotators can increase the risk of injuries in judokas. Discrete analyses are usually performed in time series data, but they can have biases by removing trends, so other approaches have been proposed to avoid these biases such as statistical parametric mapping (SPM) and principal component analysis (PCA). This study analyzed the asymmetry in the shoulder rotators in female judokas, comparing dominant (D) vs. non-dominant (ND) upper limbs. Methods: For this, 11 elite athletes (age: 20.1 ± 2.9 yrs.; experience: 4.0 ± 0.5 yrs.; body mass: 66.0 ± 14.6 kg; height: 1.6 ± 0.1 m; BMI: 24.8 ± 4.3 kg/m2), were evaluated in an isokinetic dynamometer (Cybex® Humac/Norm Dynamometer CSMI, 502140, Stoughton, MA, USA). All participants performed the concentric (CON/CON) isokinetic evaluations of internal and external rotation of the shoulder in 60°/s and 180°/s angular velocities. Results: There was no significative asymmetry between IR vs. ER at 60°/s; similar results were observed at 180°/s when analyzed by PCA or SPM methods (p > 0.05 for all comparison). There was no difference between peak torque at 60°/s or 180°/s (p > 0.05 for all comparison). Conclusions: no asymmetry was observed in IR and ER in elite female athletes, regardless of the analysis method.